2001
DOI: 10.1111/1467-9396.00269
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Exports: Regional Differences between Developing and Industrialized Countries

Abstract: This study uses a large panel of industrialized and developing countries to investigate the link between exchange rate volatility and exports. Although the empirical literature on this relationship is extensive, a clear consensus about its nature and importance is yet to emerge. Using fixed-and random-effects models to capture cross-country differences, pooled export equations are estimated for the entire panel and various subsets of countries. The results, which are robust across different volatility measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 15 publications
6
77
1
4
Order By: Relevance
“…A subsequent analysis by Grier and Smallwood (2007) reports a significant role for exchange rate uncertainty for developing countries' exports as well as a strong role for income uncertainty in most countries. Their results for developing countries provide support to earlier studies including Arize, Osang and Slottje (2000), Sauer , Bohara (2001) who report negative effects of exchange rate uncertainty on trade flows for developing countries Cheong, Mehari, Pattichis and Williams (2002) study on exchange rate volatility and U.K exports revealed that exchange rate volatility negatively affects export trade. No evidence was found to support the theoretical proposition that exchange rate uncertainty has a positive impact on international trade.…”
Section: Literature Reviewsupporting
confidence: 82%
“…A subsequent analysis by Grier and Smallwood (2007) reports a significant role for exchange rate uncertainty for developing countries' exports as well as a strong role for income uncertainty in most countries. Their results for developing countries provide support to earlier studies including Arize, Osang and Slottje (2000), Sauer , Bohara (2001) who report negative effects of exchange rate uncertainty on trade flows for developing countries Cheong, Mehari, Pattichis and Williams (2002) study on exchange rate volatility and U.K exports revealed that exchange rate volatility negatively affects export trade. No evidence was found to support the theoretical proposition that exchange rate uncertainty has a positive impact on international trade.…”
Section: Literature Reviewsupporting
confidence: 82%
“…More recent studies, which have either included a wider range of both advanced and developing countries or have approached the issue with greater statistical sophistication, have tended to find adverse effects of exchange rate volatility on trade, mainly in developing countries but also in advanced countries. Examples of such studies include Sauer and Bohara (2001), Dell'Ariccia (1999), andChowdhury (1993).…”
Section: Earlier Work On Determinants Of Exchange Rate Volatilitymentioning
confidence: 99%
“…Arize et al (2000) examined the impact of exchange rate volatility in 13 developing countries and found a significant negative effect. In another study, Sauer and Bohara (2001) focused on 22 developed and 69 developing countries and found a negative impact of exchange rate volatility on the aggregate exports of the examined developing countries. Grier and Smallwood (2007) examined the impact of exchange rate volatility on the aggregate export of nine developed as well as nine developing countries.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, a limited number of studies considered the possibility of a different impact of the mentioned factors in countries with different levels of development (e.g. Arize et al, 2000;Sauer & Bohara, 2001;Caglayan & Di, 2010). Recently, researchers focused on developing countries and assessed the impact of exchange rate volatility.…”
Section: Introductionmentioning
confidence: 99%